Critical sizes of standing nuclear burning waves in systems with external control - Leleko, Yu.Ya.; Gann, V.V. (Вопросы атомной науки и техники, 2020)
The theory of standing waves of nuclear combustion in reactors having a flat, cylindrical or spherical shape of the core is developed. A spherical standing wave occurs when nuclear burning propagates radially from the center of the sphere, and ²³⁸UO₂ fuel moves to the center and is removed from the system. The stability limits of standing waves of nuclear burning are investigated. It has been established that for standing waves there are minimum (critical) sizes at which they exist. Mathematical modeling of standing waves using the MCNPX code was carried out and critical sizes of standing waves of various symmetries were determined.